Macroprudential Policies to Enhance Financial Stability in the Caucasus and Central Asia - Khandelwal, Padamja (Departmental Papers; Departmental Paper ;, 2022)
Limited economic diversification has made the economies of the Caucasus and Central Asia particularly vulnerable to external shocks. The economies in the region are heavily reliant on oil and mining exports as well as remittances. In some countries, tourism and capital flows also play a prominent role in aggregate economic activity.